Tibial osteotomy as a mechanical model of primary osteoarthritis in rats - Britzman,D; Igah,I; Eftaxiopoulou,T; Macdonald,W; Bull,AMJ (Scientific Reports, 2018)
This study has presented the rst purely biomechanical surgical model of osteoarthritis (OA) in rats, which could be more representative of the human primary disease than intra-articular techniques published previously. A surgical tibial osteotomy (TO) was used to induce degenerative cartilage changes in the medial knee of Sprague-Dawley rats. The presence of osteoarthritic changes in the medial knee compartment of the operated animals was evaluated histologically and through analysis of serum carboxy-terminal telepeptides of type II collagen (CTX-II). In-vivo biomechanical analyses were carried out using a musculoskeletal model of the rat hindlimb to evaluate the loading conditions in the knee pre and post-surgically. Qualitative and quantitative medial cartilage degeneration consistent with OA was found in the knees of the operated animals alongside elevated CTX-II levels and increased tibial compressive loading. The potential avoidance of joint inammation post-surgically, the maintenance of internal joint biomechanics and the ability to quantify the alterations in joint loading should make this model of OA a better candidate for modeling primary forms of the disease in humans.